2020
DOI: 10.46378/irjst.2020.020105
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Medicinal and Aromatic Plants Growing in Libya and Their Therapeutic Properties.

Abstract: Plants are a rich source of diverse metabolites that have been traditionally used for thousands of years all over the world, providing safer and inexpensive therapeutic option for millions of people in developing countries including Libya. Many types of medicinal plants growing in Libya possess significantly important curative activities and have been traditionally used for treatment of chronic diseases such as diabetes and cancer, as well as their biological activities such as antibacterial, antifungal, antip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Biopolymers are naturally occurring polymers produced by living cells of animals, plants, and microorganisms, either polysaccharides, protein, or even polyesters (Figure 3) [96][97][98]. The ideal biopolymer for any medical application would have many characteristics, such as: non-toxic, does not evoke an inflammatory or immunological response, is easily sterilized, has an acceptable shelf life, and can be easily processed to its final form [26,99].…”
Section: Biopolymer-based Materials In Obstetrics and Gynecological Applicationsmentioning
confidence: 99%
“…Biopolymers are naturally occurring polymers produced by living cells of animals, plants, and microorganisms, either polysaccharides, protein, or even polyesters (Figure 3) [96][97][98]. The ideal biopolymer for any medical application would have many characteristics, such as: non-toxic, does not evoke an inflammatory or immunological response, is easily sterilized, has an acceptable shelf life, and can be easily processed to its final form [26,99].…”
Section: Biopolymer-based Materials In Obstetrics and Gynecological Applicationsmentioning
confidence: 99%
“…Malassezia species are the most common fungal species in mammalian skin, and they are the best-studied fungal species in skin conditions include atopic dermatitis and dandruff 129 . Some studies have reported that inflammation caused by the overgrowth of Malassezia may worsen gastric ulcers, weakening the immune system and changing the cell-surface signaling [130][131][132][133] . Therefore, an abundance of Malassezia species in pancreatic ductal adenocarcinoma tumors may be medically relevant.…”
Section: Carcinogenic Fungimentioning
confidence: 99%
“…In traditional medicine, the plant species Jatropha mollissima (Euphorbiaceae) is used for a wide variety of purposes, including as an anti-inflammatory remedy ( de Queiroz Neto et al, 2019 ), antibacterial treatment ( Bastos-Cavalcante et al, 2020 ), antioxidant protection ( Dias et al, 2019 ), anthelmintic action ( Abogmaza et al, 2020 ), kidney protection ( Iqbal and Yahya, 2021 ; Omer Iqbal et al, 2021 ), liver protection ( Iqbal et al, 2022 ), heart protection ( Iqbal et al, 2021 ), and appetite suppression ( de Albuquerque et al, 2007 ). The significance of J. mollissima in counteracting anxiety and depression has not been studied, despite the many research documenting the plant’s beneficial effects on health.…”
Section: Introductionmentioning
confidence: 99%